Market reactions to the closest peer firm's analyst revisions. Issue 4 (7th June 2018) - Hope, Ole-Kristian; Zhao, Wuyang
Abstract : Prior analyst literature focuses on the impact of financial analysts on the firms they cover, and prior information-transfer literature concentrates on the externalities of information provided by management. This paper fills gaps in both streams of literature by examining the focal firm's market reactions to the closest peer firm's (identified by product similarity) analyst revisions. We find that the focal firm's stock price reacts to the closest peer's analyst revisions made by analysts who are not covering the focal firm. The focal firm's cumulative abnormal return for a five-day window centered on the revision date is 0.54% higher if the peer firm's analyst revision magnitude is in the top decile than if it is in the bottom decile. Cross-sectional tests show that the sensitivity of the focal firm's market reactions to the peer firm's revisions increases with the revision informativeness and the similarity between the focal firm and the peer firm. In addition, we find that focal firms do not react to peer firms' revisions in industries with strong competition where the competitive effects cancel out the spillover effects. Finally, we find that the focal firm's market reactions can predict its own future analyst revisions, suggesting that the reactions are at least partially rational.